Abigail, the breeze fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2004)
Abigail the Breeze Fairy has been blown off-course without her wispy wind feather.
"Little Apple."
RL2.
006-009.
Accelerated Reader AR
Keywords: Fairies -- Juvenile fiction; Feathers -- Juvenile fiction; Lost articles -- Juvenile fiction; Weather -- Juvenile fiction; Villages -- Juvenile fiction; Lost and found possessions -- Fiction; Fantasy fiction